Islam, women, and politics: The demography of Arab countries - Makhlouf-Obermeyer, Carla (Population and development review, 1992)
The article examines the three propositions underlying the interpretations: that Arab countries do poorly in terms of demographic indicators, that this is due to Islam, and that the impact of Islam operates through the way in which it defines a low status for women. It reviews the available data on fertility and health in Arab countries and examines the claim that Islam is a pronatalist religion. (DSE)